Comparison of brain and cranial nerve morphology between eyed surface fish and blind cave fish of species Astyanax mexicanus - Rodrigues, Fábio Ribeiro, 1990 (2013)
Tese de mestrado. Biologia (Biologia Evolutiva e do Desenvolvimento). Universidade de Lisboa, Faculdade de Ciências, 2013